Economic analysis of oil palm fresh fruit bunch production among independent smallholders in Johor, Pahang and Perak, Malaysia - Yunus-Junaid, Busayo Rashidat (2013)
The study analyzed the comparative advantage of Fresh Fruit Bunch (FFB) production among independent smallholders. The independent smallholders have been found to contribute significantly to FFB production despite facing the same input and output market prices as the other categories of plantation owners. At present in Peninsular Malaysia, there is no longer room for land expansion for oil palm; this makes it necessary to increase yield on the existing land. The independent smallholders form the focus of this research because they are the first to be adversely affected if there are downward pressure on prices of CPO and upward pressure on prices of inputs. However, they will be spared if they produce efficiently and at reasonable returns. The study will assist in determining the area where improvement can be effected in order to increase private profitability. The analytical framework used for this research was the Policy Analysis Matrix (PAM).It was used to measure resource use efficiency (DRC), social profitability (SCB) of the independent smallholders as well as to estimate the indicators of government policy interventions like the Nominal Protective Coefficient (NPC) and the Effective Protection Coefficient (EPC). Farm budget on input requirements was important for this analysis and data was collected from 147 independent smallholders in three states through the use of questionnaires. Secondary data were also collected from government ministries,departments, bulletin and various agencies. The result of the estimation of the ratios revealed that the DRC of Johor, Pahang and Perak was 0.02, 0.03 and 0.04 while the SCB of the three states was 0.04, 0.05 and 0.07 respectively. The study proves that both methods provide similar ranking where Johor emerges as the most efficient state. Thus,independent smallholders were found to have comparative advantage in FFB production and were socially profitable and private profit is positive in all the states. After 50% decrease in output and 55% increase in input price simulations, the independent smallholders in the different states were still having comparative advantage.The result of the analysis of government protection indicators showed that in terms of NPC of output, Johor, Pahang and Perak have the values of 1.03, 1.01 and 1.05 respectively which indicate that there is implicit subsidy to the production of the output of the independent smallholders. The NPC of input is 1.15 for each of the states which imply that the independent smallholders are paying 15% more for their tradable input than they would if they had been able to obtain them at their parity prices. The result suggests that government policy is increasing input cost for the production of FFB. The result of the EPC is 1.03, 1.00 and 1.05 respectively for Johor, Pahang and Perak. The EPC for all the state is approximately 1, this shows there is no intervention or the net impact of various distortions in both the input and output markets result in a neutral effect on the value added. It implies that FFB production of the independent smallholders under export parity condition is competitive.